Safety Misbehaviour and Its Effect Towards Safety Performance of Construction Projects - Othman, I. (Springer, 2020)
The construction industry, mainly the infrastructure projects, in the world reported the highest frequency of industrial accidents, mostly among the frontline workers. Domestic and international disaster-related reports indicate that the workers have high risk associated with poor safety behaviour as a major cause of accidents. Those accidents resulted in inferior project performance with works delays and financial losses due to safety procedures that need to be followed, such as project stop-work orders and payment for injury treatment cost for the workers involved. Therefore, this study assesses the causal factors of safety misconduct in construction projects that might affect the safety performance through the application of structured questionnaire and case study of an infrastructure construction project. The statistical techniques including relative importance index (RII) and average index (AVI) were used to analyse the data gathered, while the Statistical Package for the Social Sciences (SPSS) was used to measure the Spearmanâs rank correlation between four different groups of respondents, the Cronbachâs alpha (reliability test), and validity of the study. Based on the highest impact factors identified, a framework of safety behaviour control management was proposed to improve the safety performance at the construction project. The study concludes with the conclusion on the data attained and recommendations for the improvement of safety practices in construction projects. Â© Springer Nature Singapore Pte Ltd 2020.